The Experimental and Motivational Factors Affecting Needs in Mobile-based Food Information for Foreign Tourists Traveling in Thailand - Trakulmaykee, Numtip (Journal of Thai Hospitality and Tourism, 2016)
Tourism is a source of revenue in Thailand and the most important factors in sustainable tourism is the consequent frequency of revisit. Foreign tourists in Thailand often face problems with their food because of restrictions imposed by their religions, beliefs, preferences, and health concerns. These problems tend to shorten the travel period and discourage revisit, especially for foreign tourists who have food allergies. These are problems that could possibly be reduced by providing the appropriate food information on mobile devices. Such information should be relevant to tourists’ existing consumed behaviors. Therefore, this study aims to investigate the factors of information needs in Thai food for users of mobile devices. The study employed convenience sampling using a questionnaire to collect data from 497 foreign tourists at Suvarnabhumi Airport in Thailand. The study employed descriptive statistics and regression analysis in a quantitative approach. The results revealed that technological experience influences information needs generally on mobile devices, while the experience of Thai food is not a factor in foreign tourists’ need for such information about Thai food specifically. In addition, needs in Thai food information on mobile devices are influenced by three motivation factors: health concern, learning desire, and sensory appeal. The results suggest that excitement is not a factor in foreign tourists’ needs in mobile-based information about Thai food. Finally, the result shows the high level of foreign tourists’ need for mobile-based Thai food; in particular of for information about menu ingredients and cooking methods.